Solution-phase vertical growth of aligned NiCo2O4 nanosheet arrays on Au nanosheets with weakened oxygen–hydrogen bonds for photocatalytic oxygen evolution. Issue 10 (5th March 2020) - He, Suisui; Chai, Jian; Lu, Siyu; Mu, Xijiao; Liu, Ruitong; Wang, Qiang; Chen, Fengjuan; Li, Yuee; Wang, Jingang; Wang, Baodui
Abstract : We demonstrate the synthesis of vertically arranged NiCo2 O4 –Au–NiCo2 O4 sandwich-type heterojunctions with weakened oxygen–hydrogen bonds as an efficient photocatalyst for visible-light water oxidation. Abstract : Vertical heterojunctions of two-dimensional (2D) semiconducting materials have attracted more and more research interest recently due to their unique optical, electrical, and catalytic properties and potential applications. Although great progress has been made, vertical integration of the layered materials formed by 2D semiconductor nanosheets and 2D plasmatic metal nanosheets remains a huge challenge. Here, we demonstrate for the first time a solution-phase growth of vertical plasmatic metal–semiconductor heterostructures in which aligned NiCo2 O4 nanosheet arrays vertically grow on a single Au nanosheet, forming vertically aligned NiCo2 O4 –Au–NiCo2 O4 sandwich-type heterojunctions with hierarchical open channels. Such vertical NiCo2 O4 –Au–NiCo2 O4 heterojunctions can effectively promote the separation and transfer of a photoinduced charge. Density functional theory (DFT) studies and time-resolved transient absorption spectroscopy show that electrons transfer from NiCo2 O4 to Au, and the formation of the heterojunction weakens the H–O bond of H2 O. Due to the unique structure and superiority of the component, the vertical NiCo2 O4 –Au–NiCo2 O4 heterojunctions exhibit significant activity with an O2 production rate of up to 33 μmol h −1 and long-term stability for photocatalytic water oxidation. We calculated the apparent quantum efficiency (AQE) to be 21.9% for NiCo2 O4 –Au–NiCo2 O4 heterojunctions at the wavelength λ = 450 ± 10 nm, which is higher than that of NiCo2 O4 nanosheets (10.9%), Au nanosheets (0.96%) and other photocatalysts. The present study paves the way for the controlled synthesis of novel vertical heterojunctions based on 2D semiconductor nanosheets and 2D metal nanosheets for efficient photocatalysis.